Impacts of CAADP on Africa’s agricultural-led development - Benin, Samuel (International Food Policy Research Institute, 2016)
This paper uses panel data on 46 African countries from 2001 to 2014 to estimate the impacts of the Comprehensive Africa Agriculture Development Programme (CAADP), an agriculture-led integrated framework of development priorities in Africa, on agricultural expenditure and productivity, income, and nutrition. A difference-in-difference treatment-effects model (based on when a CAADP compact is signed and the level of CAADP implementation reached) and different estimation methods and model specifications are used. The results show that CAADP has had a positive impact on agricultural value-added and land and labor productivity. The impact on agriculture expenditure is generally negative, suggesting that there is a substitution effect between the government’s own funding and external sources of funding for the sector. The estimated impact on income and nutrition is generally insignificant. There are some puzzling results from the interaction between specific period of compact signing and level of implementation reached. Implications for maintaining the positive impacts, as well as for further research to understand the puzzling results, are discussed.